Case report: Partial regression of metastatic squamous cell carcinoma with altered azathioprine dosage after long-term use in renal transplant patient - Ormston, Tegan; Da Gama Duarte, Jessica; Quigley, Luke T.; Jackett, Louise; Whitlam, John; Behren, Andreas; Gyorki, David E. (Frontiers in Immunology, 2024)
Introduction: We report the partial regression of metastatic squamous cell carcinoma (SCC) after reduction of long-term azathioprine therapy while awaiting surgery. The patient was a 69-year-old man with a history of kidney transplantation. Moderately differentiated SCC arising in the anterior neck was initially diagnosed, followed later by poorly differentiated SCC metastases to cervical lymph nodes. Lymph node clearance was performed 28 days after a reduction in azathioprine dosage. The palpable lymph node lesion had noticeably decreased in size at the time of surgery, and subsequent histology only detected 7mm and 0.2mm deposits of poorly differentiated SCC in 2 of 5 level I nodes, and a further 10 reactive nodes from levels II and III. One positive level I and another benign level II/III node, demonstrated necrosis, histiocytic infiltration and fibrosis, interpreted as features of regression. Hence, we investigated the role of immune cells in the partial regression of metastatic cutaneous squamous cell carcinoma (SCC) after reduction of long-term azathioprine therapy while awaiting surgery. Methods: Multispectral immunohistochemistry using custom markers was performed on regions of interest of excised cervical lymph nodes, encompassing the entire SCC deposit and the surrounding adjacent stroma to quantify to number and types of immune cells present.Results: Multispectral immunohistochemistry revealed the heavy infiltration of activated T cells in the tumour, as well as PD-L1+ antigen-presenting cells in the surrounding adjacent stroma, suggesting an immunologically mediated partial regression.Discussion: We hypothesize that this reaction was triggered by azathioprine dose reduction. Dose modification of long-term immunosuppressive medications in patients with a transplantation history who later develop SCCs warrants further investigation.